LiHSO4/SiO2 as a New, Efficient and Reusable Catalytic System for the Chemoselective Conversion of Aldehydes to Acylals under Solvent-Free Conditions - Abdolkarim Zare; Alireza Hasaninejad; Esmael Rostami; Ahmad Reza Moosavi-Zare; Maria Merajoddin; Azam Arghoon; Nasrin Pishahang; Mohsen Shekouhy (E-Journal of Chemistry)
A highly efficient, green and expeditious solvent-free method is described for the chemoselective conversion of aldehydes to the corresponding acylals in excellent yields, using acetic anhydride in the presence of catalytic amount (20 mol%) of silica-supported LiHSO4. Ketones does not react under these reaction conditions. LiHSO4/SiO2 can be recovered and reused without any significant loss of its catalytic activity.